Hypertonic Disease, Prevalence in the Bukhara Area (Small) and the Effect of Therapy - Saidovich, Kadirov Bekhruzbek (Journal of Science in Medicine and Life, 2024)
Prevalence hypertension diseaseamong population makes 20,2%. Including among women hypertension diseasethere are 20,2% of cases, among men of 20,66%. Thus many patients irregularly accept treatments. Only 23,23% of women and 15,38% of men daily accept hypotensive preparations.